Iron homeostasis: transport, metabolism, and regulation. Issue 4 (July 2016) - Guo, Shanshan; Frazer, David M.; Anderson, Gregory J.
Abstract : Purpose of review: Iron is essential for normal cellular function and many diseases result from disturbances in iron homeostasis. This review describes some of the recent key advances in iron transport and its regulation, how this relates to iron-related disorders, and emerging therapies for these diseases. Recent findings: The iron-regulatory hormone hepcidin and its target, the iron exporter ferroportin (FPN), play central roles in iron homeostasis. Recent studies have expanded our understanding of how hepcidin is regulated in response to stimulated erythropoiesis and have added some new players to the complex network of factors that influences hepcidin expression. Novel structural insights into how FPN transports iron have been an important addition to the field, as has the recognition that some zinc transporters such as ZIP14 can transport iron. Investigations into cardiac iron homeostasis have revealed a key role for FPN, and transferrin receptor 1, which is essential for cellular iron uptake, has been shown to be critical for normal immune function. Summary: The increased understanding of mechanisms of iron homeostasis that has resulted from recent research has greatly improved our ability to diagnose and manage iron-related disorders, and has offered new therapies for this important class of human diseases.